The Identification and Reservoir Architecture Characterization of Wandering Braided River in Nanpu 1-29 Area, Bohai Bay Basin - Xueqian Pang; Cheng Xue; Yangping Liu; Li Yin; Yufeng Gao; Yanshu Yin (Geofluids)
Nanpu 1-29 Area of Jidong Oilfield in China is currently in the stage of high water cut and low recovery degree. The remaining oil development and adjustment are difficult because of the complex reservoir heterogeneity and the lack of analysis of the reservoir architecture due to the unclear river type. This study first used sedimentary background, granularity, core, and sand body distribution to determine the river type and believed it belongs to the wandering braided river. Combined with core and logging data, four types of sedimentary architectural elements were found in the study area, namely, channel bar, braided channel, floodplain, and basalt. Based on the scale measurement of many similar modern wandering braided rivers, core data, and empirical formulas, the scales of the braided rivers were determined. The quantitative relationships among the scale of the braided river, the channel bar, and the braided channel were established. With this constraint, the reservoir architecture was anatomized. The results showed two filling types of the braided channels, including sandy filling and muddy filling. The combination patterns of the channel bars and the braided channels could be divided into three types, namely, superimposed, standalone, and contact, and the contact type was the primary type. On the whole, it showed the geometric morphological characteristics of the flat top convex at the bottom of the channel bar and the flat bottom convex at the top of the braided river channel. A careful measure of the architectural element was executed. The length of the single braided flow belts was 365.16-1349.72 m, and the width was 270.57-1160.54 m. The channel bar’s length was distributed 158.89-318.32 m, and the width was distributed 75.97-116.41 m. The braided river’s width was distributed 16.81-180.05 m. The length and width ratio of the channel bar was concentrated between 2 and 4, which manifested wide bar and narrow river channel mode. Finally, the static distribution model and dynamic response curve were compared to verify the correctness of the reservoir architecture characteristics to guide the subsequent development of the oilfield.